Analysis of the correlation between deformational plagiocephaly and neurodevelopmental delay. Issue 1 (January 2018) - Hussein, Mohammed Ahmed; Woo, Taeyong; Yun, In Sik; Park, Hanna; Kim, Yong Oock
Summary: Background: Deformational plagiocephaly (DP) refers to cranial asymmetry resulting from uneven external forces. A strong association exists between DP and developmental delay. We investigated the effect of DP severity on developmental delay. Methods: Between 2010 and 2016, data from 155 patients with DP were reviewed retrospectively. Two indices were used to evaluate the deformation quantitatively: cranial index (CI) and cranial vault asymmetry index (CVAI). The Bayley Scales of Infant Development-II was used to evaluate the neurodevelopment of patients. Results: According to the CI of the study population, 2 patients showed scaphocephaly, 12 showed mesocephaly, and 141 showed brachycephaly. For CVAI, 10 patients showed values of <3.5, 10 patients showed mild deformity (3.5–6.25), 27 patients showed moderate deformity (6.25–8.75), and 108 patients showed severe deformity. The means of the mental development index (MDI) and psychomotor development index (PDI) were 91.69 ± 16.8 and 92.28 ± 17.59, respectively; after the exclusion of patients with confounding factors, the values were 96.26 and 92.9, respectively. The Spearman correlation coefficients between MDI and CI and CVAI were −0.019662 and 0.118916, respectively, whereas for PDI, the values were −0.195428 and −0.012386, respectively. Conclusions: There was a statistically significant neurodevelopmental delay in patients with DP. However, accelerated neurodevelopment was also encountered in many patients. MDI was found to be more affected by multiple confounding factors than PDI, whereas PDI was only affected by congenital anomalies. There was no definitive relationship between the severity of DP and the degree of developmental delay in our study group.